Periprocedural 3D imaging of the left atrium and esophagus: comparison of different protocols of 3D rotational angiography of the left atrium and esophagus in group of 547 consecutive patients undergoing catheter ablation of the complex atrial arrhythmias - Starek, Zdenek; Lehar, František; Jez, Jiri; Wolf, Jiri; Kulik, Tomas; Zbankova, Alena; Novak, Miroslav (The international journal of cardiovascular imaging, 2016)
A new method in creating 3D models of the left atrium (LA) and esophagus before catheter ablation of atrial arrhythmias is 3D rotational angiography (3DRA) of the LA. The purpose of this retrospective study was to test various acquisition protocols of the 3DRA and attempt to define the parameters influencing the success of the protocols. From August 2010 to November 2014, 3DRA of the LA using the Philips Allura FD 10 X-ray system was performed in 547 consecutive patients using right atrial and left atrial protocols. Visualization of the esophagus was performed after oral administration of a contrast agent. Patients were monitored for success (creation of a useful 3D models) and evaluated for a number of parameters affecting the success of 3DRA. The success of the RA protocol was 88.89 % with and 91.91 % without esophagus imaging. The success of the LA protocol was 97.42 % with and 94.54 % without esophagus imaging. The only factor reducing the success of the RA protocol was BMI; the LA protocol was not influenced by any factor. Ventricular fibrillation induced in two patients was successfully treated with defibrillation. 3DRA of the LA is a reliable method that supports catheter ablation of complex atrial arrhythmias. The LA protocol with esophagus imaging was significantly more reliable than the RA protocol; the other protocols were comparable. The RA protocol may be negatively affected by high BMI. Simultaneous imaging of the esophagus is safe and feasible, and the LA protocol can be recommended.
Keywords: senioři; index tělesné hmotnosti; Models, Cardiovascular; Catheter ablation of arrhythmias; modely kardiovaskulární; Reproducibility of Results; Contrast Media; Radiographic Image Interpretation, Computer-Assisted; johexol; reprodukovatelnost výsledků; angiografie; Computer Simulation; Heart Atria; Retrospective Studies; Complex atrial arrhythmias; Predictive Value of Tests; počítačová simulace; Iohexol; katetrizační ablace; Middle Aged; mužské pohlaví; kontrastní látky; prediktivní hodnota testů; 3D rotational angiography of the left atrium; Esophagus; Body Mass Index; srdeční síně; Catheter Ablation; ženské pohlaví; rentgenový obraz - interpretace počítačová; Angiography; Acquisition protocols; retrospektivní studie; Humans; zobrazování trojrozměrné; fibrilace síní; lidé středního věku; Imaging, Three-Dimensional; Image integration; Female; Aged; Atrial Fibrillation; ezofágus; lidé; Male